Segmental Odontomaxillary Dysplasia in a Pediatric Patient: Case Report - Brenes Valverde DDS, Karen; Castro Mora DDS, Sergio; Ulate Jiménez DDS, Joseph (Odovtos - International Journal of Dental Sciences, 2016)
Segmental Odontomaxilar dysplasia is an uncommon pathology development that defects in the maturation of bone, teeth and gingiva one of the quadrants of the maxilla. Dentoalveolar expansion presents complex on the affected side with gingival enlargement, agenesis of one or two premolars, delayed eruption and malformation of the molars. Mucocutaneous upper lip edge blurred, upper lip hypopigmentation, hypertrichosis, erythema, and pigmentation unilateral: facial alterations were also described in a few cases, among those found. For a 3-year presents clinical, histological and radiological features described for this disease is reported and early treatment of this rare condition.